How Does Social Media Impact the Number of Citations? An Altmetric Analysis of the 50 Most-Cited MicroRNA Articles - Pala, Mukaddes; Demirbilek, Mahmut; Pala Acikgoz, Nilgun; Dokur, Mehmet (European Journal of Therapeutics, 2021)
Objective: Altmetric analysis is web-based a metric analysis. Social media platforms affect medical literature over the last few years. The altmetric Attention Score (AAS) is an automatically calculated metric for monitoring social media. This study aimed to determine the correlation between AAS and the number of citations received from important articles published in the last 11 years with microRNAs. Methods: MicroRNA as a search term was entered into the Web of Science database to identify all articles. The most 50 cited articles were analyzed by Topic, Journal Name, First Author, Publication Year, Citation, Average Citation Per Year (ACPY), Impact Factor (IF), Quartile (Q) Category, H Index, and AAS. Results: Altmetric explorer identified 45.911 articles as being referred to online. Correlation analysis revealed that there was a weak correlation between AAS and the number of citations (p<0.15), while a very strong correlation was found between the number of citations and ACPY (p<0.01). Conclusion: These results give some clues about the articles studied did not lose their currency. They are cited regularly each year so they are very popular in academia. This study provides a detailed list of 50 most cited microRNA articles and social media interest using the Altmetric.com database. miRNAs can be used in the diagnosis, prognosis, or treatment of various diseases.